Gold Mines of Osseous Engineering: Unveiling the Potential of Marine Sponge Biomaterials - Nagendrasai, Kurapati; Krishnani, Kishore Kumar (Chronicle of Bioresource Management, 2024)
Marine life and biodiversity are a rich source of possible new goods for mankind. Surprisingly, marine creatures remain a largely untapped resource for biotech applications. It is well recognized that compounds from marine sponges that are sedentary animals of the Porifera class have enormous therapeutic properties. Sponges feature a rich calcium phosphate-containing scaffold over which new cells develop due to their porosity and 3D grain structure making them appealing as bone replacements. Most species have an effective linked porous design facilitating fluid movement that aids in filtering large volumes of water to capture nutrients while also being similar to an ideal bone scaffold. Sponges contain spongin, which is similar to vertebral collagen, the most often employed natural polymer for tissue regeneration. Finally, sea sponges’ osteogenic characteristics are enhanced by their mineral content, which includes bio-silica and other chemicals that can support cell proliferation while also stimulating bone formation and mineralization.